2018
DOI: 10.1021/acs.jpcc.8b00608
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Usual Interpretation of the Structure and Ground State of Cu2+-Layered Perovskites

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
140
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(164 citation statements)
references
References 88 publications
(272 reference statements)
24
140
0
Order By: Relevance
“…18 For transition metal difluorides it was found that the high-pressure phase transition sequence differs considerably between ions of similar size, but with different d electron count, as witnessed by comparing MnF2 (d 5 system) 8,19 and CoF2 (d 7 electron count). 20 Moreover for d 9 cations (Cu 2+ , Ag 2+ ) the high-pressure polymorphism is strongly influenced by structural distortion arising from an uneven occupation of the eg orbitals (often referred to as the Jahn-Teller effect) 28 as well as strong spin-spin magnetic interactions. 24 In this context the phase transitions of zinc difluoride are of interest, as the Zn 2+ cation can be viewed as a non-magnetic (3d 10 electronic configuration) counterpart of Mn 2+ , Co 2+ , and Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…18 For transition metal difluorides it was found that the high-pressure phase transition sequence differs considerably between ions of similar size, but with different d electron count, as witnessed by comparing MnF2 (d 5 system) 8,19 and CoF2 (d 7 electron count). 20 Moreover for d 9 cations (Cu 2+ , Ag 2+ ) the high-pressure polymorphism is strongly influenced by structural distortion arising from an uneven occupation of the eg orbitals (often referred to as the Jahn-Teller effect) 28 as well as strong spin-spin magnetic interactions. 24 In this context the phase transitions of zinc difluoride are of interest, as the Zn 2+ cation can be viewed as a non-magnetic (3d 10 electronic configuration) counterpart of Mn 2+ , Co 2+ , and Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Layered hybrid compounds have drawn great attention as a new generation of high performance materials due to their interesting physical and chemical properties obtained through the combination of organic and inorganic materials at the molecular level [1][2][3]. They consist of a wide range of inorganic anion chains, alternating with a large variety of organic cations as building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of such hybrid materials is therefore large, and so offers a wide range of structures, properties, and potential applications [6][7][8][9][10][11]. More specifically, hybrid layered compounds based on the perovskite structure are interesting materials due to their potential application in solar cells [2,3]. However, the toxicity and chemical instability of halide perovskites limit their use.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid metal-organic compounds based on the perovskite structures are of increasing interest due to their potential use for solar cells. 1,2 However, toxicity and chemical instability issues of halide perovskites still remain as the main drawbacks for use in solar cells. The crystalline structure of compounds of the type (C n H 2n+1 NH 3 ) 2 MCl 4 , where n ¼ 1, 2, 3 .…”
Section: Introductionmentioning
confidence: 99%